Is it beneficial to the state to provide insulin-treated diabetic patients with public funds for self-monitoring blood glucose? - Larisa Dmitrievna Popovich; Marina Vladimirovna Shestakova; Elena Georgievna Potapchik; Alexander Yur'evich Mayorov; Olga Konstantinovna Vikulova (Сахарный диабет)
Background. In Russia, the prevalence of diabetes continues to increase with the growing diabetes epidemic. In recent years, the paradigm of diabetes treatment has been changing, with patients increasingly becoming equal participants in the treatment process, through the introduction of self-monitoring blood glucose (SMBG). Several clinical studies have demonstrated a positive relationship between SMBG and the decline of the epidemiological and economic burden of diabetes. At present, the procurement of public funds for SMBG is below the specified level in Russia. Aims. To investigate the potential macroeconomic benefits of public health resource allocation and the use of planned state investments to fund SMBG in insulin-treated diabetic patients. Materials and methods. This study was conducted with data from insulin-treated diabetic patients. The epidemiological burden of this cohort was determined by the following indicators: the number of patients and the incidence of complications resulting from diabetes, disability, mortality, age and sex. The economic benefits were evaluated by the implementation of two measures: (1) procurement of public funds for the purchase of means for SMBG in patients with insulin-treated diabetes and (2) the use of highly accurate blood glucose metres. To evaluate economic burden, the epidemiological burden was translated into monetary terms using cost-of-illness. Economic benefits were defined as reductions in economic burden. Results. The economic benefits of public-funded blood glucose test strips for insulin-treated diabetic patients exceeded the required additional investments for their purchase by 1.5 fold. A significant reduction in the inaccuracy of blood glucose metres from 20% to 10% may reduce the economic burden by 9.36 billion RUB. The combined state benefits from the implementation of both measures would significantly decrease the economic burden of diabetes to 29.2 billion RUB. Conclusions. Increased procurement of public funds for SMBG in insulin-treated diabetic patients would bring economic benefits that far exceed the required investments.